Global Smartphones Sales May Have Peaked - Mongardini, Joannes (IMF Working Papers; Working Paper ;, 2020)
Global smartphone sales may have peaked. After reaching nearly 1.5 billion units in 2016, global smartphone sales have since declined, contributing negatively to world trade in 2019 and suggesting that the global market may now be saturated. This paper develops a simple model to forecast smartphone sales, which shows that sales are likely to decline further. As tech companies shift to embedded services (cloud computing, content subscriptions, and financial services), the impact on global trade may also be shifting in favor of services exports mostly from advanced economies.